2013
DOI: 10.1016/j.celrep.2013.05.027
|View full text |Cite
|
Sign up to set email alerts
|

miR-294/miR-302 Promotes Proliferation, Suppresses G1-S Restriction Point, and Inhibits ESC Differentiation through Separable Mechanisms

Abstract: The miR-294/miR-302 microRNAs promote the abbreviated G1 phase of the embryonic stem cell (ESC) cell cycle and suppress differentiation induced by let-7. Here we evaluated the role of the Retinoblastoma (Rb) family proteins in these settings. Under normal growth conditions miR-294 promoted the rapid G1-S transition independent of the Rb family. In contrast, miR-294 suppressed the further accumulation of cells in G1 in response to nutrient deprivation and cell-cell contact in an Rb dependent fashion. We uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 39 publications
10
99
0
Order By: Relevance
“…The first group of miRNAs was reported to be highly expressed in undifferentiated hESCs but significantly downregulated upon differentiation, such as miR302s [43][44][45]. In our studies, these miRNAs were upregulated in undifferentiated H9 cells after ADAR1 knockdown.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 55%
See 2 more Smart Citations
“…The first group of miRNAs was reported to be highly expressed in undifferentiated hESCs but significantly downregulated upon differentiation, such as miR302s [43][44][45]. In our studies, these miRNAs were upregulated in undifferentiated H9 cells after ADAR1 knockdown.…”
Section: Adar1 Knockdown Dramatically Alters Mirna Repertoiressupporting
confidence: 55%
“…We first excluded the role of transcriptional regulation of ADAR1 on miRNA processing. On one hand, loss of ADAR1 had no effect on the expression of oct4, sox2, nanog and rex1 (Supplementary information, Figure S1D and Table S1), which are known as upstream regulators of the pri-miR302 promoter [45], excluding the possibility that the upregulation of miR302s is caused by upregulation of ESC-specific transcriptional factors in ADAR1 KD H9 cells. On the other hand, we found that knockdown of ADAR1 had no significant effect on the promoter activity of pri-miR302 (Supplementary information, Figure S5C), suggesting that ADAR1 is unlikely to be involved in the transcriptional regulation of pri-miR302.…”
Section: Adar1 Knockdown Promotes Processing Of Pri-mir302s To Maturementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these ESC-specific miRNAs can strongly promote or directly induce the reprogramming of somatic cells to pluripotency [70][71][72][82][83][84]. Mechanistically, these miRNAs have been shown to regulate various cellular processes, including cell cycle, differentiation, mesenchymal-to-epithelial transition (MET), epigenetic regulation, cell signaling and vesicular transport [82,[85][86][87][88][89][90][91], all of which are critical for the establishment and maintenance of pluripotency.…”
Section: Reprogramming the Somatic Cells Into Pluripotent Cells Or Otmentioning
confidence: 99%
“…The proliferation ability of ESCs is closely related to the regulation of ESC cell cycle, and ESCs are characterized with a short G1 period [3]. Some of the somatic cells like bone marrow, liver, and skin cells, have a greater regeneration and proliferation potential with short G1 period, while most of the other somatic cells regeneration potential is considered to be low with a long quiescent G0 phase and the proliferation ability is regarded as poor [3]. Cell cycle regulation has two main restriction point, G1/S restriction point and G2/M restriction point.…”
Section: Introductionmentioning
confidence: 99%